2020
DOI: 10.1002/adfm.202001232
|View full text |Cite
|
Sign up to set email alerts
|

Organoid Polymer Functionality and Mode of Klebsiella pneumoniae Membrane Antigen Presentation Regulates Ex Vivo Germinal Center Epigenetics in Young and Aged B Cells

Abstract: Antibiotic-resistant bacteria are a major global health threat that continues to rise due to a lack of effective vaccines. Of concern are Klebsiella pneumoniae (K. pneumoniae) that fail to induce in vivo germinal center B cell responses, which facilitate antibody production to fight infection. Immunotherapies using antibodies targeting antibiotic-resistant bacteria are emerging as promising alternatives, however, they cannot be efficiently derived ex vivo, necessitating the need for immune technologies to deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 88 publications
(127 reference statements)
0
47
0
Order By: Relevance
“…Tunable microenvironments in combination with proper immune cell types or organoids will provide unprecedented opportunities to investigate organ physiology and immune response ex vivo, and to test and implement novel therapeutic strategies. [ 47,48 ]…”
Section: Discussionmentioning
confidence: 99%
“…Tunable microenvironments in combination with proper immune cell types or organoids will provide unprecedented opportunities to investigate organ physiology and immune response ex vivo, and to test and implement novel therapeutic strategies. [ 47,48 ]…”
Section: Discussionmentioning
confidence: 99%
“…antigen-specific bnAb development, whether they have an impact on B-cell somatic hypermutation and T FH cell functions, and whether they can break through clonality bottlenecks that restrict the engagement of the large diversity of B-cell repertoire and memory responses. Emerging ex vivo cellular and acellular technologies (for example, organoids 28,[64][65][66] and acellular antibody discovery pipeline 67 ) that could be integrated with nanovaccine research in both in vivo and ex vivo settings can reduce the nanovaccine discovery timeline, impact on the dynamics of germinal centres and memory B-cell re-activation, and elucidate mechanisms to overcome poor immunity in the elderly population 68 .…”
Section: Review Article | Focusmentioning
confidence: 99%
“…The immune system is highly intricate and is still one of the most challenging systems to study. In order to recapitulate such complex microenvironment, lymph node organoids were developed in MMP-sensitive, defined PEG hydrogels using Naïve B cells and 40LB stromal cells (genetically modified to express CD40 ligand and produce B cell-activating factor) [118]. The study revealed that maleimide group, but not vinyl sulfone and acrylate, when used as end-group functionality in PEG hydrogels, sustained B cells' survival and germinal center-like induction.…”
Section: Other Organoidsmentioning
confidence: 99%